PENERAPAN METODE SQ3R UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN ARTIKEL SISWA KELAS XII TKJ 1 SMKN 1 POSO - Hasan, Irna Trisma (BAHASANTODEA, 2017)
The objectives of this research are (1) to describe the application of SQ3R method to improve reading comprehension of class XII TKJ 1 SMKN 1 Poso, (2) to describe the result of SQ3R method to improve reading comprehension of SMKN 1 Poso student's article. The type of this research is classroom action research following Kemmis and Mc model. Taggart, which is carried out cyclically through 4 stages, namely planning, action, observation, and reflection. Location of research in class XII TKJ 1 SMKN 1 Poso, research subjects are researchers themselves and students of class XII TKJ 1, amounting to 26 people. The study was conducted in academic year 2017/2018, ie during the month of June to August 2017. Technique of collecting data using test and non test. The reading comprehension test has been adapted to the stages of the SQ3R method, whereas the non-test technique uses an observation sheet and documentation. Data analysis techniques using quantitative and qualitative techniques. To test the validity of the test the researchers used expert judgment and grid reading comprehension tests. As for the validation test sheet validity with member check technique and the grating of the observation sheet. To reveal the results of research the researchers used 3 steps data analysis according to Milles and Hubberman namely: data reduction, data presentation, and conclusions and verification data. The result of the research shows that the application of SQ3R method can improve the reading comprehension of the students of class XII TKJ 1 SMKN 1 Poso, this is shown by the students, (1) in the survey stage the students are able to find the outline of the text content and determine the main idea of the paragraph. ) at the question stage the student is able to make a question using the 5W + 1H, (3) principle, at the read stage the student is able to answer the previous question, (4) at the recite stage the student is able to find the important points in the reading and summarize the contents of the article with using their own language, (5), students are able to review the contents of the article by recalling the questions and answers that have been compiled. Stages in the SQ3R method are related to each other. The result of the SQ3R method can improve the learning achievement of students' understanding comprehension, with the following indicators: (1) the reading comprehension value of the students rises from pre-action, cycle I, and Cycle II, (2), the total number of completed students also rises by pre-action, cycle I, and cycle II. The average increase in test results on pre-action 60, 76%, increased by 30.77 in the first cycle to 76.15%, and increased by 46.15% in the second cycle average to 82, 57%, up by 6, 24%.